Isolation, Determination and Characterization of Taro (Colocasia esculenta) Starch (Biological Sciences - PJSIR, 2005)
The starch content of taro (Colocasia esculenta) was determined using DNS colourimetric, acid-hydrolysis and enzymatic methods. Starch content varied from 80.3 to 81.3% as determined by DNS colourimetry. For the extraction of taro starch, different techniques were used. It was found that there was a noticeable improvement in the yield of starch using the freeze-thaw method. The various physicochemical properties of the extracted starch were also compared with the starch obtained by ammonia and alkali extractions. It was found that the hydration capacity, swelling volume, moisture absorption, freeze-thaw stability, as well as swelling power, were generally higher while solubility was lower of the freeze- thaw extracted starch than that extracted by ammonia and alkali. The DNS colourimetric method is recommended as a simple method for the determination of taro starch